Peer Tutoring: Developing Writing in College Education - Alzate-Medina, Gloria Mercedes; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2010)
This article presents partial results of a qualitative research on the Project of Inquiry (PRIN) that takes place in the Psychology Degree Program at Javeriana University. This project is a formative experience focused on the importance of learning investigative abilities, through academic writing. The research was based on peer-tutoring interactions with 85 ethnographic records, which were subjected to an open and axial codification, in accordance to guidelines developed by Strauss and Corbin. The records were organized in emerging categories for their interpretation, in order to establish the potential significance of the pedagogic interaction. The results established the advantages of peer-tutoring in the integral progress of students and specifically the promotion of reading and writing abilities at a College level.